Menuju Haji yang Efisien dan Berkeadilan: Optimalisasi Sistem Pendaftaran dan Pengelolaan Waiting List Jemaah Haji di Jawa Barat - Marliza (POKJANAS Bekerja Sama Biro Perencanaan dan Penganggaran, Sekretariat Jenderal Kementerian Agama RI, 2024)
The Hajj pilgrimage is the fifth pillar of Islam that is dreamed of by every Muslim throughout the world. In Indonesia, enthusiasm for performing the Hajj is very high, but it is accompanied by a long waiting list that can last for decades. This causes various problems and injustices for Hajj pilgrims. This policy paper aims to examine the problem of Hajj waiting lists in Indonesia and offer solutions for optimizing the registration system and managing waiting lists more efficiently and fairly. This study uses qualitative methods with literature studies, statistical data analysis, and interviews with relevant stakeholders. The result is that various factors cause long hajj waiting lists, such as limited hajj quotas from the Saudi Arabian government, a registration system that is not yet optimal, and a lack of transparency in managing the waiting list. Therefore, this policy paper offers several solutions for optimizing the registration system and waiting list management, including (1) Increasing the Hajj quota from the Saudi Arabian government through diplomacy and negotiation; (2) Implementation of an integrated and transparent online Hajj registration system; (3) Implementation of a fair and accountable priority system for Hajj pilgrims; and (4) Increasing education and information for Hajj pilgrims regarding waiting lists. The conclusion is that optimizing the registration system and management of the Hajj waiting list through the solutions proposed in this policy paper is expected to create a more efficient and fair Hajj pilgrimage for all Muslims in Indonesia.